Fabrication and electromagnetic wave absorption performance of quartz ceramics containing inductive SiC screens. Issue 10 (July 2019) - Meng, Zhen; Li, Rui; Zheng, Mengyao; Yuan, Guojian; Zhou, Guangyou; Guo, Jia; Zhu, Xiaotao; Ren, Guina; Li, Xiangming
Abstract: For developing an interference type electromagnetic wave absorbing material with good ageing and temperature resistances, inductive SiC screens (ISCS) are formed by filling SiC powder in the highly–ordered and well–connected big pore channels of the quartz (SO) ceramics fabricated by inverse replication of polylactic acid (PLA) templates. The electromagnetic wave absorption performance of the ISCS/SO composites is greatly affected by the dimension of ISCS which could be easily adjusted by changing the lattice structure dimension of the templates. In the frequency range of 8.0–18.0 GHz, the ISCS/SO composites with the side length of SiC columns of 3 (5) mm and the interval between SiC columns of 9 (15) mm obtain a mean reflectivity of about −10 dB, little increased mean reflectivity of −9.6 (−9.7) dB after heat treating at 800 °C for 100 h, gradual increased mean reflectivity of −8.1 (−7.1) dB after heat treating at 900 °C for 100 h, and fast increased mean reflectivity after heat treating at temperatures above 1000 °C. The ISCS/SO composites are good structural interference type absorbing materials that could be used for a long time at temperatures below 800 °C and for a limited time at temperatures above 900 °C.